Effect of vanadium and heat treatment on the corrosion behavior of ferritic stainless steel - Eren, Hulya; Aksoy, Mustafa; Korkut, Mehmet H.; Erbil, Mehmet (Carl Hanser Verlag, 2008)
In this study, the corrosion behavior of ferritic stainless steel with 1 wt. % V was determined by AC impedance technique and mass-loss method. The samples were cast, then shaped by forging. 0.1 M H2SO4 and 0.3 M HCl acid solutions were used as corrosive environments. The samples were classified into three groups. In the first group, samples were unhomogenized, remaining in production condition. The second and third group samples were exposed to homogenization at 1100 degrees C for 30 min or 180 min, respectively, and then quenched. SEM investigations were performed for samples exposed to corrosion for 30 min and 360 min. Subsequently, it was determined that adding vanadium increased corrosion resistance in chloric acid solution but has no helpful effect in sulphuric acid solution, according to AC impedance test results. The mass-loss results showed that vanadium increased corrosion resistance of ferritic stainless steel in both solutions.
Auswirkung von Vanadium und Wärmebehandlung auf das Korrosionsverhalten von Ferritischem Nichtrostendem Stahl
Keywords: Carbide-Forming Elements; Fe-Cr Alloys; Repassivation Kinetics; Dissolution Kinetics; Passivation Kinetics; Pitting Corrosion; Pit Solutions; Molybdenum; Mo; Resistance